Resource islands of Salix cupularis facilitating seedling emergence of the companion herbs in the restoration process of desertified alpine meadow, the Tibetan Plateau. (1st July 2021) - Li, Qi; Shen, Xudong; Huang, Qian; Sun, Feida; Zhou, Jiqiong; Ma, Xiao; Ran, Zhouya; Chen, Youjun; Li, Zhou; Yan, Yanhong; Zhang, Xinquan; Gao, Wuchao; et al.
Abstract: Salix cupularis is a common shrub for ecological restoration of the desertified alpine meadow on the Tibetan Plateau. However, the effect of S. cupularis on spatial heterogeneity of soil resources ( i.e ., resource islands effect) has not been systematically evaluated, and the influence of shrub patches on the rehabilitation of understory herbs has also been unknown. In this study, we randomly selected S. cupularis individuals in the early restoration stage of desertified alpine meadow, where the three native forages ( Elymus nutans, Elymus sibiricus and Festuca sinensis ) were sown at different microsites around S. cupularis to explore the effects of S. cupularis on soil resources and emergence rates of the native forages. The results showed that S. cupularis significantly increased SWC (soil water content), C (carbon) and N (nitrogen) nutrients ( p  < 0.01) and enzyme activities ( p  < 0.05) under canopy compared with the bare land, and the improvement performed better in the topsoil (0–5 cm) than in the subtop-soil (5–15 cm). Moreover, the soil properties were affected significantly by microsites around S. cupularis, resulting in regular changes of SWC, nutrients and enzyme activities in different microsites (Shrub center > Middle of canopy radius > Bare land). In addition, there are significant regression relationships between emergence rates and enriching soil water, C and N nutrients, so the emergence rates of native forages under canopy may be improved significantly with the enriched soil resources, especially for E. nutans . As a result, S. cupularis is a suitable pioneer shrub for the vegetation restoration of desertified alpine meadow on the Tibetan Plateau, because it could not only shape the enrichment of soil resources under canopy, but also facilitate emergence of companion forages in the process of vegetation restoration. Highlights: The significant resource enrichment was found under shrub canopy of Salix cupularis. Soil properties under canopy changed regularly with microsites rather than shrub size. S. cupularis had better nurse effect on the emergence rates of Elymus nutans than that on Elymus sibiricus and Festuca sinensis. E. nutans may have higher ecological adaptability to be used for desertified meadow restoration accompanying with S. cupularis in the desertified alpine meadow.